MENGUKUR OBJEKTIVITAS LIPUTAN MEDIA DENGAN RUMUS COEFFICIENT OF IMBALANCE (Studi Kasus Hasil Penelitian Metode Analisis Isi Kuantitatif Pemberitaan Kampanye Pemilu 1999 di Harian Jawa Pos dan Republika Terhadap Partai Golkar dan PDI-P) - Effendy, Rochmad (Universitas Merdeka Malang, 2016)
AbstractGeneral election which aims at selecting the best national leadership for the next five year office term is peoples democracy party event which requires the nation attention. Mass media plays an important role to have the event successful by covering general election campaign, along with its rule and procedures, the political party program statements, the prospective candidate track record, and general election irregularities in independent, neutral and impartial manner. By doing so, media functions as voter education to enable them to choose the candidate rationally based on unbiased and balanced media coverage. In addition, media have to control and monitor general election procedures violation committed by each general election stakeholders. If it is the case, the general election will run freely and fairly. To achieve this, media should cover objectively by means separating his subjective opinion from the fact being covered. This type of media coverage, among other things, will undoubtedly bring about free and fair general election. The paper attempts to describe the relation between media and politics, as well as the objectivity of East-Java Province based Jawa Pos newspapers sand Muslim-oriented Republika daily during general election 1999 campaign period. Besides, it tries to measure their coverage objectivity employing the Coefficient of Imbalance formulae especially with regard to the parties namely the presumed pro status quo Golkar party and the reformist PDI-P party. The paper puts its emphasis on the discussing the objectivity method for media coverage using quantitative content analysis. The papers concludes by presenting an example of content analysis result using the formulae on the 1999 general election media coverage which found that each newspaper was biased to each the political party with Jawa Pos favored PDI-P and Republika supported Golkar.Keywords: Objectivity, Content Analysis, Coefficient of Imbalance, Inferences, judgmentDOI :Â https://doi.org/10.26905/nomosleca.v2i1.340